Bacillus subtilis in defense mode: Switch-like adaptations to protistan predation - van Gestel, Jordi; Koo, Byoung-Mo; Stürmer, Vanessa S.; Garriga-Canut, Mireia; Wagner, Jonas; Zanon, Andrea; Gross, Carol (Proceedings of the National Academy of Sciences of the United States of America, 2025)
Single-cell eukaryotic predators in the soil are a primary cause of bacterial cell death. Yet, most functional genomic studies on soil bacteria have been performed without predation, thereby selecting for phenotypes impacting growth rather than survival and biasing our view on the ecological factors driving genomic evolution. Here, we study how predation by the ubiquitous amoebal predator Dictyostelium discoideum affects Bacillus subtilis’ growth and survival using both a genome-scale mutant screen and de novo evolution of resistance. We show that predation-related genes (many not previously identified) promote survival by enabling filament or aggregate formation, thereby outsizing D. discoideum and slowing or preventing ingestion. Importantly, we find that predation resistance is costly, causing a trade-off between growth and survival. B. subtilis navigates this trade-off through switch-like adaptations, where cells switch back-and-forth between a slow-growing resistant state and a fast-growing susceptible state. These behaviors are controlled through both genotypic and phenotypic switches, with a central role for the Spo0A phosphorylation cascade, whose ancestral function may have been to evade or slow predation. Taken together, we uncover how the antagonist selection pressure imposed by predation is an important ecological driver of phenotypic heterogeneity in B. subtilis.